ASEAN Energy Firms’ Financial Fortitude: Past Geopolitical Insights For Iran-Israel Challenges - Kesuma, Muhammad Ramadhani; Irianto, Ellen D. Oktanti; Ariswati, Lusiana Desy; Henrika, Margareth; Widaryo, Chandika Mahendra; Aini, Rohana Nur (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Geopolitical crises, including the Gulf tensions (2019–2020) and the Russia-Ukraine conflict (2022), have profoundly disrupted the financial performance of ASEAN energy firms, offering critical insights for navigating the ongoing Iran-Israel conflict. This study investigates the influence of financial ratios—Debt to Equity Ratio (DER), Total Asset Turnover Ratio (TATO), and Liquidity Coverage Ratio (LCR)—on financial performance, measured through Current Ratio (CR) for liquidity and Net Income (NI) for profitability, across 101 energy firms in Indonesia, Malaysia, the Philippines, Thailand, and Singapore from 2019 to 2023. Utilizing panel data regression with data sourced from the Wall Street Journal, the findings demonstrate that LCR significantly enhances both liquidity and profitability, ensuring resilience amid market volatility. Conversely, TATO negatively impacts liquidity, reflecting trade-offs in asset efficiency, while DER shows no significant effect, suggesting prudent debt management. Firm Size increases profitability but reduces liquidity due to operational complexity. These results advance theoretical understanding of financial resilience in emerging markets and provide actionable liquidity-focused strategies for managers and policymakers to address current geopolitical uncertainties, fostering robust financial stability.